Essence of Muhammad Hatta’s democracy: relevance to the development of regional autonomy - JALIL, MAT (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The purpose of this article is to critically and systematically find out, inventory, and interpret the concept of Muhammad Hatta’s democracy.The method used is library research. Data analysis was carried out by using elements of qualitative research method in the field of philosophy, which includes historical methods, descriptions, internal coherence, and hermeneutics. The theory used is Colar Gould, which is a four theses work of the concept of freedom. The results show a concept of freedom that must be more widely understood on the availability of social and material conditions, legal politics, as well as socioeconomic equality, reciprocating equality of participation. RESUMEN El propósito de este artículo es descubrir, inventariar e interpretar de manera crítica y sistemática el concepto de democracia de Muhammad Hatta. El método utilizado es la revisión bibliográfica. El análisis de datos se realizó utilizando elementos del método de investigación cualitativa en el campo de la filosofía, que incluye métodos históricos, descripciones, coherencia interna y hermenéutica. La teoría utilizada es Colar Gould, que consta de cuatro tesis del concepto de libertad. Los resultados muestran un concepto de libertad que debe entenderse más ampliamente sobre la disponibilidad de condiciones sociales y materiales, políticas legales, así como la igualdad socioeconómica y reciprocidad de participación.